(untitled) (Economics and region, 2022)
The article systematizes and summarizes existing problems in building innovative business models in the conditions of modern realities, analyzes approaches to defining the concept of an innovative ecosystem, identifies potential, and offers recommendations for improving and stimulating the domestic innovation process. An innovative business model is proposed, which is suitable for Ukraine in the conditions of modern realities and is used by the leading countries of the world to solve the problems of transition from a formal to an effectively functioning innovation ecosystem. The purpose of the study is to generalize the existing knowledge and practices of forming innovative business models, develop recommendations for improving and stimulating the domestic innovative potential, adding elements to the selected innovative business model and the possibility of adapting companies in the conditions of modern realities. Foreign and domestic scientists and practitioners pay great attention to the problems of business modeling, in particular, the interpretation of the essence of concepts. Today’s modernized economy is characterized by interdependent, separately operating economic counterparties of a self-regulated innovative ecosystem, which must quickly respond to changes in the market situation and consumer demand, is characterized by flexible branch principles of production organization and clearly structured processes of development, market entry, production and service of sold products potential consumers. There is a difference between the traditional model of value creation, based on the cooperation of leading business stakeholders, and the formation of business models of innovation ecosystems on a common open innovation platform. The strategy for the development of the innovative sphere of Ukraine until 2030 shows solutions in this direction. The purpose of the strategy is to build a national innovation ecosystem, ensure flexible and fundamental application of creative ideas to innovative products and services, increase the innovative level of the national economy, which creates favorable conditions for development, increase the number of real developments in the field of innovative activity, increase economic income from them, attract investments in innovative activities. The main factors of the effectiveness of innovative ecosystems are determined by the degree of formation of innovative business models of micro-diversified companies, which reflect the quality of interaction of interested parties, realize digitalization of technologies and cover economic development.